Effect of vibration and noise on spark ignition engines of methanol fuel blended with gasoline - Erdiwansyah, .; Mahidin, .; M. S. M., Sani; Rizalman, Mamat; Asri, Gani; Munawir, .; Susmanto, . (CSIR-NIScPR, India, 2022)
Nowadays, various types of engines are manufactured by the automotive industry, especially for cars that have huge demand all over the world in general, and Malaysia in particular. The vibration and noise continue to be a significant problem among the various issues th at exist in the engine to date. In this re search, tests were performed on a four-cylinder gasoline engine of methanol fuel blended with gasoline fuel at distinct quantities (between 5% and 10%) and motor speeds of 1000, 1200, and 1400 rpm. The findings indicate that the methanol gasoline combination has the highest vibration and noise between 1200 and 1400 rpm, while gasoline has the lo west vibration and noise between 1000 and 1400 rpm. The modifications in the combustion system owing to the characteristics of the fuel mixture used have an essential impact on the engine’s vibration and noise.